Short Communication Beneficiation of Malakand Graphite Ore (Biological Sciences - PJSIR, 2008)
. On benefication of an indigenous graphite ore of Malakand, Pakistan, on laboratory and pilot plant scale by froth flotation technique, the ore, which initially contained 17% graphitic carbon, was upgraded to a graphite concen- trate containing 84% graphitic carbon with more than 70% recovery. The concentrate conforms to the specifications of the foundry grade graphite. Maximum recovery is achieved at pH 7.5 and pulp density of 33% solids with a dose  of 0.14 kg/ton sodium silicate, 2.2 kg/ton kerosene oil and 0.02 kg/ton pine oil.